PENGARUH SERVICE QUALITY TERHADAP KEPUASAN PELANGGAN PADA LEMBAGA PENDIDIKAN SOLOCOM DI SURAKARTA - Ningsih, Suhesti (Universitas Muhammadiyah Surakarta, 2011)
The purpose of this research is to know the service quality and consumer satisfaction to the students of LPK Solocom Surakarta. The method of the research is survey. The population is 200 students and the sample is 75 students. Data was collected by using questionnaire and analyzes by regression. Based on the research result, concluded that (1) the quality of education service is not satisfaction yet: (2) tangible, empathy, reliability, responsiveness, and assurance give effect to consumerâs satisfaction of LPK Solocom Surakarta. The results of study indicate that the assurance variable positively affected by consumer satisfaction.Â While the variable tangible, reliability, responsiveness and empathy didnât have an effect on consumer satisfaction.Â For the F test, thatâs all independent variable affected the consumerâs satisfaction.Â